Persepsi Masyarakat Non-muslim di Kecamatan Denpasar Barat terhadap Bank Syariah - Kurnia, Thiaz Annasha; Tripalupi, Lulup Endah (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the perceptions of non-Muslim communities in West Denpasar towards Islamic banks. This study used a descriptive-type research to analyze the perceptions of non-Muslim community towards Islamic banks in West Denpasar. The population of this study was non-Muslim communities in West Denpasar, the sample used consist of 400 people obtained by Slovin formula and the data collection method used questionnaires. The results shows that the perception of non-Muslim community from the cognitive aspect obtained a score of 24,946, thus it could be categorized as favorable. The perception of non-Muslim community from the affective aspect obtained a score of 8,777, thus it could be categorized as unfavourable. Meanwhile, the perception of non-Muslim community from the conative aspect obtained a score of 8,980, thus it could be categorized as favourable. It can be concluded that the perception of non-Muslim communities in West Denpasar towards Islamic banks is good.